An investigation into causes of success and failure in small businesses within the Department of Social Development in the Eastern Cape - Petrus, Henry George (Rhodes University, Faculty of Commerce, Rhodes Business School, 2009)
The failure rate of small business initiatives in South Africa is phenomenal, and much is needed to unravel the causes contributing to such failures. Yet small businesses are playing a vital part in our global economy and in particular in terms of job creation and poverty eradication. There are internal as well as external factors that play a significant role in determining the success of these small businesses. In South Africa much emphasis is placed by national, provincial and local governments on small and medium enterprises (SMEs) to drive wealth creation and black economic empowerment. Therefore, an investigation into the factors contributing to the success and failure of SMEs is of vital importance. The South African government's poverty eradication strategy, which is driven by the Department of Trade and Industry (DTI), allocated funds for job creation programmes as a method to combat poverty and more importantly, to develop young entrepreneurs. Among the seven departments mandated by DTI was the Department of Social Development. Since the birth of the new democracy, this department has transformed from offering a traditional remedial method of service delivery to an integrated developmental approach. This approach included extensive community work, which includes job creation and economic empowerment through the establishment of small businesses. Given the availability of funding, the inability to spend fiscal budgets as per allocation as well as the charity element of receiving involved, it is important to explore whether factors contributing to the success of these SMEs are any different to the traditional business strategies. In this study, the researcher gave special consideration to the social capital element and its contribution in the context of community support as well as the ability of SMEs to become sustainable business ventures over time. The research study aims to highlight unique factors contributing to the success and failures of SMEs established by the Department of Social Development and in doing so hopes to manifest an improved understanding of the management of these SMEs. In chapter one, the researcher gives a brief description of the activities of the Department of Social Development and its mandate to establish SMEs for job creation. A brief explanation regarding the context of the problem that was investigated is also given. Chapter two provides a detailed theoretical overview of the study, focusing in particular on factors contributing to the success and failure of small businesses. In chapter three, the research design and the various instruments used are discussed. Here, emphasis is placed on procedural issues and ethical considerations. The validity and reliability of the research is strongly motivated. In chapter four the research results are discussed. Chapter five aims to discuss the findings of the research with reference to the theoretical overview outlined in chapter two. Lastly, chapter six makes recommendations to the various stakeholders who may benefit from this research. These recommendations are the most important objectives of the research and should add value with regards to the management of SMEs in future, with special reference to the Department of Social Development in the Eastern Cape.
Keywords: South Africa -- Dept. of Social Development; South Africa -- Dept. of Trade and Industry; Small business -- South Africa -- Eastern Cape; Small business -- South Africa -- Eastern Cape -- Growth; Business enterprises -- Economic aspects -- South Africa -- Eastern Cape; Economic development -- South Africa -- Eastern Cape; Job creation -- South Africa